PENGARUH PENGGUNAAN TEKNIK RELAKSASI NAFAS DALAM TERHADAP PERUBAHAN INTENSITAS NYERI PADA PASIEN POST OP SECTIO CAESAREA - Hijriyati, Yoanita; Utami, Yuli; Elimanafe, Wehelmina (Journal of Nursing and Midwifery Sciences, 2024)
Postoperative pain management is very important to be carried out comprehensively to overcome nursing problems such as pain problems. Relaxation techniques are independent nursing interventions to reduce pain intensity, improve lung ventilation and increase blood oxygenation. The act of deep breath for relaxation is easy to learn and contributes to lowering or relieving pain by reducing muscle pressure and anxiety. This study aims to determine the effect of using deep breathing relaxation techniques on changes in pain intensity in post-op caesarean section patients at Budhi Asih Hospital. This study used a quantitative design with a Pretest-Posttest One Group Intervention Design. The population in this study werepost-op caesarean section patients at Budhi Asih Hospital. The sample in this study was 17 respondents. The sampling technique was consecutive sampling. The instrument used Numeric Rating Scale (NRS). The results showed that before the application of the deep breath relaxation technique, almost all respondents (94.1%) experienced moderate pain intensity. After the application of the technique, most of the respondents (64.7%) still experienced pain intensity of the same scale.Based on statistical tests with the Wilcoxon signed ran test, the p-value is 0.000 <a=0.05 (0.000<0.05), which means that there is an Effect of Using Deep Breathing Relaxation Techniques on Changes in Pain Intensity in Post-Op Sectio Caesarea Patients at Budhi Asih Hospital. Suggestions for health workers with this study are expected to be able to implement deep breathing relaxation techniques to reduce pain in post-op sectio caesarea patients.